Knowledge, Attitude and Perception about Adverse Drug Reaction Reporting System among Pharmacy Students in Bangladesh - Islam Rasel, Md Shamiul; Mohona, Farhana Afrin; Lira, Dilshad Noor; Kumar, Uttom; Shamsur Rouf, Abu Shara (Dhaka University Journal of Pharmaceutical Sciences, 2023)
Inadequate resources and a fragmented healthcare system in Bangladesh lead to the practice of almost non-reporting of adverse drug reactions (ADR). Pharmacists may offer service in this regard to strengthen pharmacovigilance if given the appropriate opportunity. To evaluate their preparedness, the current cross-sectional study aims to assess the knowledge, attitude and perception (KAP) of pharmacy students about the ADR reporting system. A validated self-administered and structured questionnaire was filled out online upon informed consent by 400 final-year and master-level participants from 22 public and private universities. Data analysis was done using the Statistical Package for Social Science (SPSS, v.23.0) and Microsoft Excel. The average knowledge score of the students came out as 2.93 (SD=0.6) out of 5. While fundamental knowledge regarding ADR was displayed well by the participants such as agreeing to ‘side effects and ADRs are different’ (85%), advanced conceptual understanding exhibited lacking. For example, variable like ‘distinguishing between ADR and an adverse drug event’, ‘not all ADRs are known before a drug is marketed’, and ‘before ADR reporting, drug’s association needs no confirmation’ showed 14%, 41% and 5% correctness, respectively. However, 98% of the participants emphasized the need for ADR reporting, in both serious and non-serious cases, 85% knew that anybody can report ADR and approximately the same percentage of students could identify the organization receiving reports. Less than half (47%) were familiar with the authorized ADR reporting form and 40% reportedly claimed that they knew when and how to report. The need for more relevant education about this was supported by most of the students (91.8%). Participants mostly agreed about the need for reporting and gaining more overall awareness about the ADR reporting procedure. The findings suggest that increased knowledge, training, assertiveness and practice among all stakeholders are necessary for a spontaneous ADR reporting system in the country. Dhaka Univ. J. Pharm. Sci. 22(1): 21-28, 2023 (June)